2014
DOI: 10.1182/asheducation-2014.1.318
|View full text |Cite
|
Sign up to set email alerts
|

Management of incidental splanchnic vein thrombosis in cancer patients

Abstract: A 75-year-old male with metastatic pancreatic cancer is undergoing chemotherapy with gemcitabine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Similar recurrent VTE, bleeding complications, and mortality rates, comparing incidental PE and deep vein thrombosis (DVT) with symptomatic events has been described [66,67]. However, there is limited evidence about the optimal management of isolated, incidental subsegmental PE and incidental visceral vein thrombosis (iVVT), in particular splanchnic vein thrombosis (SVT) [68]. Some observational retrospective and prospective studies have suggested a similar outcome of incidental subsegmental PE compared to patients with more proximal clots or symptomatic events [67,69], but the precise role of anticoagulation remains unknown in isolated cases.…”
Section: Treatment Of Incidental Thromboembolic Eventsmentioning
confidence: 85%
“…Similar recurrent VTE, bleeding complications, and mortality rates, comparing incidental PE and deep vein thrombosis (DVT) with symptomatic events has been described [66,67]. However, there is limited evidence about the optimal management of isolated, incidental subsegmental PE and incidental visceral vein thrombosis (iVVT), in particular splanchnic vein thrombosis (SVT) [68]. Some observational retrospective and prospective studies have suggested a similar outcome of incidental subsegmental PE compared to patients with more proximal clots or symptomatic events [67,69], but the precise role of anticoagulation remains unknown in isolated cases.…”
Section: Treatment Of Incidental Thromboembolic Eventsmentioning
confidence: 85%
“…In 85% of these patients with nonocclusive PVT, 70% showed spontaneous resolution and 19% showed resolution and reappearance with very few patients having received anticoagulation therapy. When PVT developed prior to progression of the liver disease, it was not statistically associated with increased risk of liver disease progression or decompensation 20. In contrast, an earlier series by Amitrano et al 7 in patients with more advanced cirrhosis reported 11.2% PVT incidence and 45% were symptomatic with portal hypertensive bleed, abdominal pain, and/or intestinal infarction.…”
Section: Risk Factors and Natural Historymentioning
confidence: 85%
“…Visceral thrombosis is an emergent topic in the literature (50,55,67,68,77,79-83). Due to the heterogeneity of presentation, thrombosis can be discovered incidentally through the course of the disease, in particular in patients with advanced metastatic disease, or thrombosed may present with symptoms that lead to further abdominal imaging.…”
Section: Discussionmentioning
confidence: 99%
“…These uncertainties and the lack of guidelines collectively contribute to challenging decision making in this setting. (50) Currently, most treatment algorithms regarding VT are extrapolated from studies based on patients with liver cirrhosis with/without HCC (13,18,19,51-53), owing to the increased incidence of VT in liver cirrhosis compared to PDAC.…”
Section: Anticoagulationmentioning
confidence: 99%